Notaris sebagai Pilar Pencegahan Maladministrasi Rups: Perspektif Good Corporate Governance dan Penyuluhan Hukum - Brigitte Queency Darmawan; Citra Puspa Amalia; Muhammad Daffa Zacky Parnanda; Vanessa Valencia (LPPM Institut Pendidikan Nusantara Global, 2026)
This doctrinal legal research analyzes the strategic role of Notaries in preventing maladministration in General Meetings of Shareholders (GMS) through the application of Good Corporate Governance (GCG) principles and the exercise of legal counseling authority. In the context of corporate governance, maladministration in GMS often arises from procedural irregularities, lack of transparency, or non-compliance with statutory requirements, which may later lead to legal disputes. Therefore, the involvement of Notaries is crucial not only as formal legal actors but also as preventive legal safeguards. The findings indicate that, beyond their primary function as drafters of authentic deeds, Notaries play an important preventive role in detecting and preventing maladministration during the preparation and implementation of GMS. The authority to provide legal counseling under the Notary Office Act enables Notaries to guide shareholders and corporate management in understanding and complying with applicable legal norms. Through this authority, Notaries can identify deviations in GMS procedures that are inconsistent with GCG principles and the provisions of the Company Law at an early stage. In conclusion, optimizing legal counseling by Notaries, whether accompanied by the drafting of an authentic deed or not, can serve as an effective control mechanism to ensure transparent, accountable, and legally compliant GMS implementation. This preventive function significantly minimizes the potential for future corporate disputes and strengthens overall corporate governance practices.